2004
DOI: 10.1007/s10595-005-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical activation of aluminum: 1. Joint grinding of aluminum and graphite

Abstract: Changes in the crystal structure and composition of aluminum and graphite powder mixtures in the course of their joint mechanical treatment in a vibration mill were monitored by the adsorption and X-ray diffraction techniques. It was shown that, at absorbed energy doses of 8-10 kJ/g, the grinding and mixing of aluminum with graphite is completed by the formation of an intermediate structure of Al/C composite, where aluminum showed an anomalously high reactivity. The interaction of aluminum with water was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 7 publications
0
26
0
3
Order By: Relevance
“…Formation of new, not oxidized and defective surfaces of metal in nanocomposite materials leads to high reactivity of mechanochemically synthesized composites with different reagents. A special technique 483 was designed to prevent self-ignition of nanocomposite Al-C during its first contact with air. It was shown that Al in the composite Al-C interacts with oxygen at significantly lower temperature than in case of the usual sample.…”
Section: Metal-ceramic Nanocompositesmentioning
confidence: 99%
“…Formation of new, not oxidized and defective surfaces of metal in nanocomposite materials leads to high reactivity of mechanochemically synthesized composites with different reagents. A special technique 483 was designed to prevent self-ignition of nanocomposite Al-C during its first contact with air. It was shown that Al in the composite Al-C interacts with oxygen at significantly lower temperature than in case of the usual sample.…”
Section: Metal-ceramic Nanocompositesmentioning
confidence: 99%
“…Butyagin); standard PP-1 aluminum (State Standard 5592-71) with an average linear particle diameter of 97 μm and MPG-type graphite with a specific surface of 2 m 2 /g were used as the precursors. Details of the mechanical activation of aluminum and results of investigation of the structure of the powder are presented in [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…It was shown in previous communications [1,2] that, in the processes of mechanical treatment of aluminum in mixtures with graphite, the particles of Al/C composite containing chemically active aluminum are formed. Based on the measurement results for the specific surface area of Al-C mixtures and the analysis of the shapes of X-ray diffraction spectrum lines, it was assumed [2] that the particles of Al/C composite are built from nanocrystalline blocks of aluminum and amorphous carbon.…”
Section: Introductionmentioning
confidence: 99%